Stimulating performance: A scoping review on transcranial electrical stimulation effects on Olympic sports - Friehs, M. A.; Whelan, E.; Güldenpenning, I.; Krause, D.; Weigelt, M. (Psychology of Sport and Exercise, 2022)
Transcranial electrical stimulation (tES) is widely used to explore the role of various cortical regions involved in a multitude of motor and cognitive processes. Recently, tES has been discussed as being able to potentially enhance performance in sports and even been suggested as a potential way of boosting performance in competitions. In this scoping review, we systematically investigate the literature on tES-induced performance modulations on Olympic sports. The aim is to create a critical overview of the emerging field of tES-enhanced sports performance. Further, methodological approaches, research desiderata, and potential directions for future research will be identified. The final dataset shows a large variation in methodology and a lack of research into the area. Further, partially sub-optimal choices in study design, methodology, and lacking consistency in reporting procedures may impede valid conclusions and obscured the effects of tES on Olympic sports. Consequently, we outline future directions and areas to improve research.